Grey Three-Way Decision Approach with The Change of Decision Objects - Gu, Sheng-qiang; Zhao, Huan-huan; Han, Zhi-ying (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
In practical decision problems, some decision objects may enter or exit the decision system, which will affect the decision results. To deal with dynamic decision problems with uncertain information, we construct a dynamic three-way decision method by exploiting three-way decisions, grey numbers, and grey targets. In this paper, firstly, by considering the similarity of positive and negative bullseye distances, we exploit Topsis and grey target to construct a conditional probability of three decisions. Then we propose a dynamic update rule based on the changing of the decision objects and determine the object's evaluation function and the threshold's calculation method. Finally, a case is used to verify the effectiveness and feasibility of the proposed model.